Path finding in multipath routing for mobile ad hoc networks - Wagio (2008)
Mobile ad hoc network (MANET) is a collection of wireless mobile nodes forming a temporary network. It is based on radio to radio multi-hopping and has neither fixed based stations nor a wired backbone infrastructure. It is characterized by dynamic topologies, limited bandwidth, energy constraint node and variable link capacity. Each node in the network could move on its way and cause the network topology to change frequently. There are many routing protocols proposed to find a route to the destination node in an environment with frequent topological changes. However, it is preferable in high mobility network environment to find multiple paths from the source node to the destination node. If one of the discovered routes fails, there will be still some other routes available. After all of the available routes failed, a new route construction process is carried out to find a set of new multiple routes. We propose Path-switching On-demand Multipath (PODM) routing protocol as a new multipath routing protocol. PODM tries to find more node-disjoint paths in one route construction process, during the route reply phase. It uses the multipath finding with probabilistic one step backtracking. A node which wants to send data to the destination will initiate the path setup process. This process consist of two phases, which are route request and route reply phase. The later phase will determine whether the source node will get some link-disjoint paths, node-disjoint paths or non-disjoint paths.